Information Security Problems of Computer Networks - Abdullaev Sharof Abdugafforovich (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
The article deals with the problems of information security of computer networks and the main functions of the information security system.